Ashabiyyah and poverty alleviation: Insights from Minang, Aceh, and Batak communities in North Sumatra - Hasibuan, Mhd Zulkifli; Chuzaimah Batubara; Muhammad Arif (Universitas Negeri Surabaya, 2025)
This research explores multiple dimensions of poverty, highlighting key contributing factors such as economic conditions, inadequate wages, demographic influences, and limited market opportunities. A central finding reveals how Acehnese communities address poverty by developing micro, small, and medium enterprises (MSMEs) as productive economic units. Cultural approaches play a significant role, with different ethnic groups in Indonesia adopting distinct strategies: the Acehnese emphasize family-based support, the Minang prioritize cooperation, and Batak communities value wealth, lineage, and honor. The study underscores the importance of collaborative efforts between the government, society, and family networks in poverty alleviation, placing particular emphasis on familial economic support and mutual assistance.